Engaging Students’ Autonomous Learning across Vocational Secondary Schooling: Teachers’ Role and Challenge - Beny Hamdani; Raudhatul Islam; Husnul Hotimah (English Teaching Journal and Research: Journal of English Education, Literature, And Linguistics, 2021)
In the industrial revolution 4.0., autonomous learning is considered as a desirable goal in English language teaching and learning in Indonesia. The movement towards learner-centered approaches has resulted in more emphasis on the benefits of learner autonomy in the success of English language teaching and learning. The research examines the capabilities of vocational secondary English teachers in Probolinggo, East java, Indonesia to engage students’ autonomous learning. The term capabilities refers to substantive freedom or opportunities that English teachers hold to do and to be a certain thing that they consider valuable. Data for the study were generated through interviews with twenty vocational secondary English teachers across remote area, urban area, Pesantren and state vocational secondary school. English Teachers were interviewed by autonomous learning issues based on their knowledge and understanding of these issues. Further, data were obtained from classroom observations and analysis of curriculum documents which include the national curriculum framework of Indonesia, English teachers’ syllabi and lesson plans. Data analysis is qualitative. The study revealed that vocational secondary English teachers in Probolinggo are still problematic and facing several challenging particularly in view of autonomous learning which was centered on traditional didactic and teacher-directed modes of delivery. This indicates that Indonesian vocational secondary English teachers in Probolinggo are not effectively engaged in autonomous learning in spite of their concerted efforts to do so.